Freezing expired platelets does not compromise in vitro quality: An opportunity to maximize inventory potential. Issue 3 (29th November 2019) - Johnson, Lacey; Waters, Lauren; Green, Sarah; Wood, Ben; Marks, Denese C.
Abstract : BACKGROUND AND OBJECTIVES: Cryopreservation provides an option for long‐term storage of platelet concentrates. While platelets are usually frozen as soon as practical after collection (within 2 days), the ability to freeze units at a later stage of the shelf life may improve inventory management. As such, the aim of this study was to determine the impact of freezing platelets approaching expiry (Day 5/6). MATERIALS AND METHODS: Two ABO‐matched buffy coat–derived platelets (30% plasma/70% platelet additive solution) were pooled and split to produce matched pairs (n = 8 pairs). Platelets were frozen on Day 1 after collection (cryopreserved platelets [CPPs]) or Day 5 or 6 (expired‐CPPs) at −80°C with 5% to 6% dimethyl sulfoxide. In vitro platelet quality was tested before freezing and after thawing and reconstitution in plasma. RESULTS: The majority of prefreeze parameters were equivalent for all platelet units (Day 1 vs. Day 5 or 6). Expired‐CPPs had a higher mean postthaw platelet recovery (82 ± 4%) compared to CPPs (75 ± 4%; p = 0.0021). Cryopreservation resulted in a loss of surface glycoproteins (glycoprotein (GP) Ibα, GPIIb, GPVI), an increase in activation markers (phosphatidylserine and P‐selectin) and microparticle release, compared to unfrozen platelets. However, the cryopreservation‐induced changes were equivalent in CPPs and expired‐CPPs. Functionality was measured by thromboelastography and was similar between expired‐CPPs (R‐time: 5.3 ± 0.3) and CPPs (R‐time: 5.4 ± 0.5; p = 0.7094). CONCLUSION: The phenotype and functional profile of platelets frozen at expiry were similar to platelets frozen 1 day following collection. These data suggest that expired platelets may represent a suitable starting material for cryopreservation.